Micromechanical property quantification using scanning acoustic microscopy - Wang, Y.; Spencer, P.; Misra, A.; Marangos, Orestes; Katz, J. L. (My University, 2006)
Scanning acoustic microscopy (SAM) has been extensively used for imaging micromechanical properties by the measurement of the reflection coefficient. However, for quantification of micromechanical properties, it is important that the scanning acoustic microscope is carefully calibrated. In this paper, we utilize two methods of calibration; (1) a time domain method and (2) a frequency domain method. The time domain method gives an average value of the reflection coefficient over the transducer frequency spectrum whereas the frequency domain method gives reflection coefficients as a function of frequency. Several reference materials with acoustic impedance ranging from -2 MRayl to 100 MRayl were imaged with SAM using transducer with central frequency of 30 MHz at different instrument settings. These images were analyzed to generate calibration curves utilizing the above mentioned methods. These calibration curves may be used to quantify the reflection coefficients, acoustic impedance and elastic moduli of unknown materials and interfaces.
Keywords: Bone and Bones; Bone; Mineralized collagen